Green Marketing Mix and Eco-Label Consumer Behavior, The Role of Environmental Knowledge - Hanna Meilani Damanik; Krismanto Erick Tobush Naibaho; Martin Luter Purba; Frederick Saroha Silaban; Yehezkiel Dosdoy Siagian (Penerbit Goodwood, 2026)
Purpose: This research investigates how the green marketing mix, which includes green product, green price, and green people, influences green consumer behavior towards eco-labeled goods, with environmental knowledge acting as a mediating factor. Research Methodology: A quantitative method was utilized through purposive sampling. Data were gathered via questionnaires from 200 participants knowledgeable about eco-labeled products. The examination was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 3.3. Results: The results indicate that environmental knowledge significantly and positively influences green consumer behavior. Although the direct effects of green marketing mix dimensions are not uniformly significant, their indirect effects via environmental knowledge are significant, supporting its mediating role. Conclusions: The results highlight the importance of integrating green marketing strategies with efforts to improve environmental knowledge in fostering sustainable consumption behavior. Effective marketing of eco-labeled products requires both strategic alignment and consumer awareness development. Limitations: This study is limited by the relatively small sample size and the use of purposive sampling, which may restrict the generalizability of the findings. Contributions: This study contributes theoretically by explained the mediating role of environmental knowledge in the green marketing–behavior relationship. Practically, it offers insights for firms to develop integrated strategies that align marketing initiatives with environmental education to promote the adoption of eco-labeled products.